Deteksi Kandiduria Pada Wanita Penderita Diabetes Melitus Di Puskesmas I Denpasar Barat - Brigita Elsza Liana; Ni Wayan Desi Bintari; Sri Idayani (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2023)
Diabetes mellitus is a disease associated with metabolic disorders in the body with the characteristics of an increase in the body's blood sugar levels. In people with diabetes mellitus, candiduria infection can occur due to excessive growth of Candida fungi in the urinary tract. Patients are declared candiduria if Candida is found in the urine >103 CFU/mL. The study ao aimed to determine whether candiduria occurred in women with diabetes mellitus who were examined at the West Denpasar Health Center I. The sampling technique used purposive sampling. The sample used was 53 urine using the patient's medical record data for December 2022. Sample analysis was carried out at the Parasitology and Mycology Laboratory STIKES Wira Medika Bali. Candiduria was detected by examining the number of colonies per ml of urine on Sabouraud Dextrose Agar. Identification of causative species was carried out by Gram microscopy and germ tube test. Based on the examination results, 2 samples (3.8%) were positive for candiduria and 51 samples (96.3%) were negative. Identification of Candida species known to cause candiduria in both samples was caused by C. albicans. With the characteristics of an oval, gram-positive blastospore, and a germ tube test, the formation of blastospores is like germinating cells. Based on the results of the study, it is expected that respondents maintain body immunity, blood sugar levels, and cleanliness of the genital area so as to reduce the risk of candiduria.